A double-blinded, randomized controlled clinical trial of hydrogen inhalation therapy for idiopathic sudden sensorineural hearing loss - Okada, Masahiro; Ogawa, Hideo; Takagi, Taro; Nishihara, Eriko; Yoshida, Tadashi; Hyodo, Jun; Shinomori, Yusuke; Honda, Nobumitsu; Fujiwara, Takashi; Teraoka, Masato; Yamada, Hiroyuki; Hirano, Shin-ichi; et al. (Frontiers in Neuroscience, 2022)
Background: Hydrogen (H2) has been reported to be effective in reducing hearing loss due to several causes in animal studies. However, no study has examined the effectiveness of H2 in treating hearing loss in humans. Thus, we investigated whether H2 is effective for the treatment of idiopathic sudden sensorineural hearing loss (ISSNHL). Materials and methods: We conducted a double-blind randomized controlled trial at six hospitals between June 2019 and March 2022. The study protocol and trial registration have been published in the Japan Registry of Clinical Trials (jRCT, No. jRCTs06119004). We randomly assigned patients with ISSNHL to receive either H2 (H2 group) or air as a placebo (control group) through inhalation combined with the administration of systemic glucocorticoids and prostaglandin E1. The primary outcome was the hearing threshold and changes in hearing threshold 3 months after therapy. In contrast, the secondary outcomes included the proportion of patients with a good prognosis (complete recovery or marked improvement). Results: Sixty-five patients with ISSNHL (31 and 34 in the H2 and control groups, respectively) were included in this study. The hearing threshold 3 months after treatment was not significantly different between the groups; 39.0 decibels (dB) (95% confidence interval [CI]: 28.7–49.3) and 49.5 dB (95% CI: 40.3–58.7) in the H2 and control groups, respectively. In contrast, the changes in hearing threshold 3 months after treatment was 32.7 dB (95% CI: 24.2–41.3) and 24.2 dB (95% CI: 18.1–30.3) in the H2 and control groups, respectively. Consequently, the changes in hearing threshold were significantly better in the H2 group than in the control group (P = 0.048). However, no adverse effects due to the inhalation of H2 gas have been reported. Conclusion: This is the first study to investigate the efficacy of H2 for the treatment of ISSNHL in humans. The results suggest that H2 therapy may be effective for ISSNHL treatment. Clinical trial registration: https://jrct.niph.go.jp/re/reports/detail/10442, jRCTs06119004.